(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Small and medium-sized enterprises (SMEs) play an important role in the development of national economies. The specificity of digital transformation in the conditions of green transition requires the disclosure of the problems and opportunities arising in their practice. Based on a conceptual framework of the digital transformation of SMEs in the context of the green transition, this study outlines some of these issues and opportunities through in-depth interviews with expert managers managing SMEs. The analysis of the results shows: the specificity of the problems of SMEs working in the field of production of organic food and bio products; the role of digitization of activities in the management of SMEs to support the transition to productions with minimal impact on the environment; the need to inform customers about the benefits of consuming products that do not endanger the environment; the need to explore the application of artificial intelligence in the field of ecological production. On the basis of these conclusions, a quantitative study of the problems and challenges faced by SMEs in the digitalization of their activities in the conditions of the green transition can be planned.